2020
DOI: 10.21203/rs.3.rs-18104/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circ_RPL23A acts as a miR-1233 sponge to suppress the progression of clear cell renal cell carcinoma by promoting ACAT2

Abstract: Background Clear cell renal cell carcinoma (CCRCC) is a prevalent urological carcinoma with high metastatic risk. Circular RNAs (circRNAs) have been identified as effective diagnostic and therapeutic biomarkers for CCRCC. This research aims to disclose the involvement of circRNA ribosomal protein L23a (circ_RPL23A) in CCRCC, and how it regulates carcinogenesis. Methods We performed quantitative real-time polymerase chain reaction (qRT-PCR) to examine circ_RPL23A, microRNA-1233 (miR-1233) and acetyl-coenzyme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…[29] asserted that circRNA_002178 enhanced tumor growth by targeting miR-328-3p to reduce the expression of COL1A1. CircRNA_103809 induced cancer-promoting function by mediating miR-4302-targeted ZNF121 level in lung cancer [30], and circ_RPL23A elevated the level of ACAT2 to retard cell progression by sequestering miR-1233 in ccRCC [31]. Our reverted assays indicated that SCARB1 attenuated the inhibitory regulation of circ_0003146 knockdown in ccRCC cells, which suggested that the oncogenic role of circ_003146 was achieved by upregulating SCARB1.…”
Section: Discussionmentioning
confidence: 92%
“…[29] asserted that circRNA_002178 enhanced tumor growth by targeting miR-328-3p to reduce the expression of COL1A1. CircRNA_103809 induced cancer-promoting function by mediating miR-4302-targeted ZNF121 level in lung cancer [30], and circ_RPL23A elevated the level of ACAT2 to retard cell progression by sequestering miR-1233 in ccRCC [31]. Our reverted assays indicated that SCARB1 attenuated the inhibitory regulation of circ_0003146 knockdown in ccRCC cells, which suggested that the oncogenic role of circ_003146 was achieved by upregulating SCARB1.…”
Section: Discussionmentioning
confidence: 92%
“…Besides, circ-ITCH was demonstrated to perform anticancer effects in ccRCC by suppressing cell invasion and migration through the miR-106b-5p/PDCD4 axis [21]. Cheng et al [22] indicated circ_RPL23A overexpression led to cell cycle, proliferation, and metastasis arrest in ccRCC by upregulating ACAT2 through abolishing miR-1233. All the findings imply the emerging role of circRNA as a biomarker in RCC.…”
Section: Discussionmentioning
confidence: 99%
“…e ccRCC has been the 13th commonly diagnosed cancer all over the world in 2020, which brings deep influence on human health [1]. At present, the biomarker study about ccRCC has made great progress, and micro-RNAs (miRNAs) are increasingly being discovered for having a function in the occupancy and growth of ccRCC [2]. miRNAs are a kind of noncoding RNAs with more than 20 nucleotides that have no potential to encode proteins [3].…”
Section: Introductionmentioning
confidence: 99%